1983
DOI: 10.1037/0022-3514.44.5.1014
|View full text |Cite
|
Sign up to set email alerts
|

Toward a more rigorous definition of social reinforcement: Some interpersonal clarifications.

Abstract: A significant portion of researchers define social reinforcers procedurally (i.e., a priori), thereby ignoring Skinner's (1953) admonition to define reinforcers empirically. The research reported in this article compared "popular" and "interpersonal" concepts of reinforcement under experimental conditions in which the two concepts imply different reinforcers. Confederates responded to hostile-dominant statements by boys, ages 8 to 14 years, with either friendly-submissive (popular) or hostile-submissive (compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…praise and approval (warmth and friendliness, in terms of the interpersonal circle; Brokaw & McLemore, 1983). Parallel findings have emerged from an extensive series of studies by Swann, demonstrating the strength and prevalence of self-verification tendencies, even among individuals with negative self-views (see Swann, 1990, for a review).…”
Section: Hostile Complementaritymentioning
confidence: 81%
“…praise and approval (warmth and friendliness, in terms of the interpersonal circle; Brokaw & McLemore, 1983). Parallel findings have emerged from an extensive series of studies by Swann, demonstrating the strength and prevalence of self-verification tendencies, even among individuals with negative self-views (see Swann, 1990, for a review).…”
Section: Hostile Complementaritymentioning
confidence: 81%
“…This distinction implies different concepts of reward as well. Lewinsohn (1974) assumed that pleasant events such as positive social responses are rewarding to everyone, whereas the interpersonal reflex model views as a reward any response that will strengthen the individual's tendency to act in accustomed ways (Brokaw & McLemore, 1983). Thus, hostile dominance would be reinforcing for depressed individuals and would lead to further self-effacing behavior, whereas positive "rewards" could even be perceived as self-dissonant.…”
Section: Stage Vi: Selective Perception and Recallmentioning
confidence: 99%
“…In any nonreciprocal dyad (i.e., in which the subject attempted to utilize hostile-dominance, hostile-submission, or friendly-dominance) we could predict less frequent use of the target response by the subject." Brokaw and McLemore's (1983) study contrasted the notion that praise and warmth are universal reinforcers with the interpersonal prediction that different reinforcers are required for different behaviors. They demonstrated that among hostile-dominant boys, hostile-submissiveness (the complementary response) elicited more hostile-dominance-whereas friendly-submissiveness (the noncomplementary response, which includes the behaviors of warmth and praise) elicited less.…”
Section: Therapist As Social Reinforcermentioning
confidence: 97%